A study of mental health of EMS personnel during COVID-19 (A qualitative study) - Sanatkhah, Alireza; Rahmani Ravari, Ali; Ghanizade Shoabjarei, Reza (Frontiers in Public Health, 2025)
BackgroundMedical staff that was under a lot of pressure and had insufficient resources and facilities during the outbreak of COVID-19. Accordingly, the present study attempts to gain a wider understanding of the reasons and factors affecting the mental health of Birjand EMS personnel during COVID-19.MethodologyThe Grounded Theory method was used in the present study. Using in-depth and free interview technique according to this theory and also, by using targeted sampling, based on the inclusion criteria, the required data was collected and adjusted from 25 personnel of this organization. The samples were selected according to theoretical saturation and using the purposive sampling method. A semi-structured interview was used as a data collection tool. Additionally, three methods of control or validation by members, analytical comparisons and the use of audit techniques were used so as to achieve the criterion of validity.ResultsBased on the results of the present study, stressful work and social environments, the risk of mistakes and occupational accidents, as well as physical disorders are known as the most important causal conditions. Undesirable salary and benefits, perceived social dignity and trust, and perceived social hope have been proposed as intervening factors. Distrust in management and cultural-educational infrastructural defects are mentioned as background conditions and reformatory measures of the government, increase in the level of public awareness, increase in the motivation of personnel, improvement of work and professional skills as action-interactions, behavioral-functional reaction and physical-psychological symptoms have been identified as outcomes.ConclusionThe mental health of personnel is formed under the influence of internal and external organizational (social) factors. The most important factor that affect it is management performance in society.